Poly-L-Arginine Induces Apoptosis of NCI-H292 Cells via ERK1/2 Signaling Pathway - Ya-Ni Wang; Ling-Ling Zhang; Xiao-Yun Fan; Sha-Sha Wu; Sheng-Quan Zhang (Journal of Immunology Research)
Cationic protein is a cytotoxic protein secreted by eosinophils and takes part in the damage of airway epithelium in asthma. Poly-L-arginine (PLA), a synthetic cationic protein, is widely used to mimic the biological function of the natural cationic protein in vitro. Previous studies demonstrated the damage of the airway epithelial cells by cationic protein, but the molecular mechanism is unclear. The purpose of this study aimed at exploring whether PLA could induce apoptosis of human airway epithelial cells (NCI-H292) and the underlying mechanism. Methods. The morphology of apoptotic cells was observed by transmission electron microscopy. The rate of apoptosis was analyzed by flow cytometry (FCM). The expressions of the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2), Bcl-2/Bax, and cleaved caspase-3 were assessed by western blot. Results. PLA can induce apoptosis in NCI-H292 cells in a concentration-dependent manner. Moreover, the phosphorylation of the ERK1/2 and the unbalance of Bcl2/Bax, as well as the activation of caspase-3, were involved in the PLA-induced apoptosis. Conclusions. PLA can induce the apoptosis in NCI-H292 cells, and this process at least involved the ERK1/2 and mitochondrial pathway. The results could have some indications in revealing the apoptotic damage of the airway epithelial cells. Besides, inhibition of cationic protein-induced apoptotic death in airway epithelial cells could be considered as a potential target of anti-injury or antiremodeling in asthmatics.